Method and system for storing logical data blocks into flash-blocks in multiple non-volatile memories which are connected to at least one common data I/O bus - WITTENBURG JENS PETER; BRUNE THOMAS (2012)
For recording or replaying in real-time digital HDTV signals very fast memories are required. For storage of streaming HD video data NAND flash memory based systems can be used. However, NAND flash memories have a slow write access, and they have unmasked production defects. Write or read operations can be carried out on complete physical data blocks only, and defect data blocks must not be used by the file system. Logical file system blocks are used which are larger than the physical data blocks. According to the invention the error reporting mechanism of the NAND flash memories is exploited. The video data is not only written to the non-volatile flash memories, but is also written to corresponding buffer slots (LFSB) of a volatile SRAM or DRAM memory operating in parallel. The video data are kept in the volatile memory until the flash memory holding the respective data has reported that its program or write operation succeeded. Once this has taken place, the data within the volatile memory can be overwritten in order to save memory capacity. If the flash memory has reported an error, the respective block (FSBD) of data is marked bad and will not be overwritten until the end of the entire recorded take has been reached. At this time, the marked video data from the volatile memory are copied to spare flash-blocks within the flash memories.